IDENTIFIKASI BAKTERI BATANG GRAM NEGATIF PENGHASIL Extended Spectrum β Lactamase (ESBL) DARI ULKUS DIABETIKUM DERAJAT I DAN II Waigner DI BANGSAL PENYAKIT DALAM RSUD ARIFIN ACHMAD PROVINSI RIAU - Ferry Anggriawan; Rita Endriani; Ligat Pribadi Sembiring (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2014)
Diabetic ulcers are open wound on the skin surface effect of neuropathy andvascular insufficiency that made the wound are often not felt by the patient , and candevelop into an infection caused by aerobic and anaerobic bacteria . Diabetic ulcersmedical patients are very susceptible infected with antibiotic-resistant bacteria likeESBL -producing bacteria. This descriptive study to detect Gram-negative bacillibacteria producing enzyme Extended spectrum beta - lactamase ( ESBL ) in diabeticulcers, are carried out using a double disc approximation Method ( DAM ) to thenumber of study subjects were 26 people with diabetic ulcers Wagner grade I and II .The results obtained ESBL producing bacteria as much as 16 samples ( 69.57 % )some of them were Citrobacter freundi , Enterobacter sp , Proteus sp , Klebsiella sprespectively – each of them are 3 isolates ( 18.75 % ) , and Pseudomonas sp ,Salmonella sp respectively – each of them are 2 isolates ( 12.5 %) .The results of theantibiotic sensitivity test showed that Gram-negative bacilli bacteria producing ESBLhave high sensitivity toward amikacin and meropenem as much as 16 samples ( 100% ) Antibiotics Betalaktam groups such as ampicillin, and third -generationcephalosporins such as cefotaxcime , ceftriaxone, and ceftazidime factually hadexperienced resistance 100% toward ESBL producing bacteria.Keywordrs : diabetic ulcers , Double disc aproximation Method ( DAM ) , Gram -negative bacilli bacteria , Extended spectrum beta - lactamase ( ESBL )